2009
DOI: 10.1016/j.abb.2009.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Akt poly-ubiquitination and proteasomal degradation in P388D1 cells by 7-ketocholesterol and 25-hydroxycholesterol

Abstract: Akt plays a role in protecting macrophages from apoptosis induced by some oxysterols Previously we observed enhanced degradation of Akt in P388D1 moncocyte/macrophages following treatment with 25-hydroxycholesterol (25-OH) or 7-ketocholesterol (7-KC). In the present report we examine the role of the ubiquitin proteasomal pathway in this process. We show that treatment with 25-OH or 7-KC results in the accumulation of poly-ubiquitinated Akt, an effect that is enhanced by cotreatment with the proteasome inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Protein ubiquitination is an important post‐translational modification that regulates various biological functions 27, 30. It has been reported that Akt undergoes K63 ubiquitination, which is a critical regulator of Akt phosphorylation 29, 30. Therefore, Akt ubiquitination (K63) was further measured in sublytic C5b‐9‐treated GMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein ubiquitination is an important post‐translational modification that regulates various biological functions 27, 30. It has been reported that Akt undergoes K63 ubiquitination, which is a critical regulator of Akt phosphorylation 29, 30. Therefore, Akt ubiquitination (K63) was further measured in sublytic C5b‐9‐treated GMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Protein ubiquitination is an important post‐translational modification regulating various biological events, such as cell proliferation and apoptosis 27–29. Many reports have confirmed that Akt undergoes lysine‐63 chain (K63) ubiquitination, which is necessary for Akt phosphorylation 29, 30. The process of ubiquitination involves three enzymes (E1–E3).…”
Section: Introductionmentioning
confidence: 99%
“…This is prevented by Akt, which phosphorylates GSK-3. In turn, 25-HC degrades Akt [36], which would derepress GSK-3 and promote SREBP-2(M) degradation. Given that δ-tocotrienol has been shown to reduce Akt activity [37,38], and 25-HC and δ-tocotrienol act synergistically ( Figure 5B), could δ-tocotrienol influence the Akt/GSK-3/Fbw7 axis of SREBP-2(M) degradation?…”
Section: Tocotrienols Act By Degrading Mature Srebp-2mentioning
confidence: 99%
“…This seems to depend on the particular in vitro model being investigated. It can induce endoplasmic reticulum (ER) stress [15] , stimulation of Akt [16] , cell proliferation through the epidermal growth factor receptor (EGFR) [17] and activation of the Toll-like receptor 4 (TLR4) [18] , to mention a few. The consensus in the published literature is that NFκB- mediated cytokine production is the main pathway responding to 7KCh-induced inflammation.…”
Section: Introductionmentioning
confidence: 99%